Store Atmospherics: A Multisensory Perspective - Spence, C; Puccinelli, N; Grewal, D; Roggeveen, A (Wiley-Liss Inc., 2014)
Store atmospherics affect consumer behavior. This message has created a revolution in sensory marketing techniques, such that across virtually every product category, retailers and manufacturers seek to influence the consumer's "sensory experience." The key question is how should a company design its multisensory atmospherics in store to ensure that the return on its investment is worthwhile? This paper reviews the scientific evidence related to visual, auditory, tactile, olfactory, and gustatory aspects of the store environment and their influence on the consumer's shopping behavior. The findings emphasize the need for further research to address how the multisensory retail environment shapes customer experience and shopping behavior. © 2014 Wiley Periodicals, Inc.